Infection Dynamics and Immune Response in a Newly Described Drosophila-Trypanosomatid Association - Phineas T. Hamilton (American Society for Microbiology, 2015)
ABSTRACT Trypanosomatid parasites are significant causes of human disease and are ubiquitous in insects. Despite the importance of Drosophila melanogaster as a model of infection and immunity and a long awareness that trypanosomatid infection is common in the genus, no trypanosomatid parasites naturally infecting Drosophila have been characterized. Here, we establish a new model of trypanosomatid infection in Drosophila—Jaenimonas drosophilae, gen. et sp. nov. As far as we are aware, this is the first Drosophila-parasitic trypanosomatid to be cultured and characterized. Through experimental infections, we find that Drosophila falleni, the natural host, is highly susceptible to infection, leading to a substantial decrease in host fecundity. J. drosophilae has a broad host range, readily infecting a number of Drosophila species, including D. melanogaster, with oral infection of D. melanogaster larvae resulting in the induction of numerous immune genes. When injected into adult hemolymph, J. drosophilae kills D. melanogaster, although interestingly, neither the Imd nor the Toll pathway is induced and Imd mutants do not show increased susceptibility to infection. In contrast, mutants deficient in drosocrystallin, a major component of the peritrophic matrix, are more severely infected during oral infection, suggesting that the peritrophic matrix plays an important role in mediating trypanosomatid infection in Drosophila. This work demonstrates that the J. drosophilae-Drosophila system can be a powerful model to uncover the effects of trypanosomatids in their insect hosts. IMPORTANCE Trypanosomatid parasites are ubiquitous in insects and are significant causes of disease when vectored to humans by blood-feeding insects. In recent decades, Drosophila has emerged as the predominant insect model of infection and immunity and is also known to be infected by trypanosomatids at high rates in the wild. Despite this, there has been almost no work on their trypanosomatid parasites, in part because Drosophila-specific trypanosomatids have been resistant to culturing. Here, we present the first isolation and detailed characterization of a trypanosomatid from Drosophila, finding that it represents a new genus and species, Jaenimonas drosophilae. Using this parasite, we conducted a series of experiments that revealed many of the unknown aspects of trypanosomatid infection in Drosophila, including host range, transmission biology, dynamics of infection, and host immune response. Taken together, this work establishes J. drosophilae as a powerful new opportunity to study trypanosomatid infections in insects.